Investigation on the use of metalens fabricated with 3D printing for ultrasound imaging in non-destructive testing - Toh, Camden Chong Han (Nanyang Technological University, 2020)
Non-Destructive Testing (NDT) is used in the analysis and inspection of an object without damaging it. NDT is commonly used to detect discontinuities in the object using methods such as Ultrasonic Testing (UT). The study aims to improve image resolution with the use of metamaterial lenses using UT to beyond Rayleigh Resolution Image Limit of λ/2 and compare with previous works. Furthermore, to test the limit of the C-scan machine to determine if the machine can detect when the distance between two defects get closer and closer with and without metamaterial lenses. Although there are past experiments done on the improvement of image resolution, the results were not comprehensive enough as the image resolution did not exceed λ/2. This study reports an improvement of image resolution using three methods of UT mainly, Pulse-Echo Method, Through-Transmission Method and Immersion Method. Different diameters and lengths of straws used as metamaterial lenses were used to be tested in the three methods for A-scan using Krautkramer USM 35 and C-scan machine using Ultrascan 5. These metamaterial lenses were evaluated in two types of specimens to determine for the best image resolution. Firstly, using different lenses to test on Aluminium block 6061 and 3D printed Aluminium. Secondly, to determine which lenses can produce better image resolution when the distance between defects get closer. The results were found to have better image resolution when metamaterial lenses were used. The resolution was also better than Rayleigh Resolution Image Limit of λ/2 with a resolution of λ/6.3. It was observed that Lens 2 produced the best image resolution. However, lens 2 was not able to distinguish the distance between defects from 0.5mm to 0.2mm apart.